2012
DOI: 10.1063/1.4752437
|View full text |Cite
|
Sign up to set email alerts
|

Phonon engineering in nanostructures: Controlling interfacial thermal resistance in multilayer-graphene/dielectric heterojunctions

Abstract: Using calculations from first principles and the Landauer approach for phonon transport, we study the Kapitza resistance in selected multilayer graphene/dielectric heterojunctions (hexagonal BN and wurtzite SiC) and demonstrate (i) the resistance variability ($50 À 700 Â 10 À10 m 2 K=W) induced by vertical coupling, dimensionality, and atomistic structure of the system and (ii) the ability of understanding the intensity of the thermal transmittance in terms of the phonon distribution at the interface. Our resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

6
39
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(45 citation statements)
references
References 28 publications
6
39
0
Order By: Relevance
“…measured G between graphene and h -BN to be 7.4 MW/m 2 K51. Similarly, this result is still more than an order of magnitude smaller than the theoretically predicted value of 187 MW/m 2 K52, and is explained as a result of random lattice-mismatch and possible contaminations at the interface51. For MoS 2 , Taube et al .…”
mentioning
confidence: 78%
“…measured G between graphene and h -BN to be 7.4 MW/m 2 K51. Similarly, this result is still more than an order of magnitude smaller than the theoretically predicted value of 187 MW/m 2 K52, and is explained as a result of random lattice-mismatch and possible contaminations at the interface51. For MoS 2 , Taube et al .…”
mentioning
confidence: 78%
“…The g-hBN interface can be more transparent to heat carrying phonons because of the similar masses of carbon, boron, and nitrogen. 35 The curvature of the graphene sheet is an additional contributor to the interface thermal resistance in g-SiO 2 . 36 Annealing contributes to the graphene sheet conforming to the substrate and hBN being atomically flat means the graphene sheet in g-hBN has lower cumulative curvature than the graphene sheet in g-SiO 2 effectively decreasing interfacial resistance in g-hBN.…”
mentioning
confidence: 99%
“…The TBC at graphene/h‐BN interfaces has been reported recently . Using first‐principles atomistic Green's function (AGF) simulations, Mao et al reported a room temperature (RT) TBC of 187 MW m −2 K −1 for a multilayer graphene/multilayer h‐BN structure. Zhang et al estimated the TBC at graphene nanoribbon/h‐BN bilayer structure to be 5 MW m −2 K −1 at RT using classical molecular dynamics (MD) simulations.…”
Section: Introductionmentioning
confidence: 99%